Kompetensi Pedagogik Guru dalam Mengembangkan Kemampuan Berpikir Kreatif Siswa di Sekolah Dasar - Muammar, Muammar; Irmayani, Irmayani; Megawati, Megawati (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
This research is motivated by the demands of the Industrial Revolution 4.0 era, which emphasizes that the younger generation should have creative thinking skills, which can then face the challenges of life in global competition in the future. This study aims to describe the role of teacher pedagogical competence in developing students' creative thinking skills in elementary schools. This type of research is descriptive with a qualitative approach. The research setting is in the Higher Class (IV, V, and VI) of SDIT Anak Sholeh Mataram. Data collection techniques with observation, interviews and documentation. Data analysis with data reduction, data presentation, and data verification. I checked the validity of the data by triangulating techniques and sources. The results of the study indicate that the role of teacher pedagogical competence in developing students' creative thinking skills in the Higher Class of SDIT Anak Sholeh Mataram has a positive relationship which is marked by the achievement of creative thinking indicators, namely: (a) the ability to produce many ideas or solutions in a short time (fluency); (b) the ability to see a problem from a different perspective and produce diverse solutions (flexibility); (c) the ability to produce unique or unusual ideas (originality); and (d) the ability to expand or develop initial ideas into more detailed concepts (elaboration).